2017
DOI: 10.1002/2016jc012448
|View full text |Cite
|
Sign up to set email alerts
|

Slope‐induced tidal straining: Analysis of rotational effects

Abstract: Tidal straining is known to be an important factor for the generation of residual currents and transports of suspended matter in the coastal ocean. Recent modeling studies and field experiments have revealed a new type of “slope‐induced” tidal straining, in which the horizontal density gradient required for this process is induced by the presence of a slope rather than by river runoff (as in classical tidal straining). Slope‐induced tidal straining is investigated here with the help of an idealized numerical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
(82 reference statements)
0
6
0
Order By: Relevance
“…To maintain effective mixing in the bottom boundary layer, some process to restore near‐bottom gradients is required, and indeed, the boundary layer over sloping topography was found to be only intermittently well‐mixed (McPhee‐Shaw, 2006; White, 1994, this study). Candidates for restratifying processes are, among many others, the along‐slope advection of stratification with the boundary current, the cross‐slope advection of buoyancy anomalies by Ekman transport, on timescales of a few days, (White, 1994, and the references therein), or, on subtidal time scales, an episodic straining of the near‐bottom isopycnals induced by the interaction of tidal currents with the sloping topography (Schulz & Umlauf, 2016; Schulz et al., 2017; Umlauf & Burchard, 2011; White, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To maintain effective mixing in the bottom boundary layer, some process to restore near‐bottom gradients is required, and indeed, the boundary layer over sloping topography was found to be only intermittently well‐mixed (McPhee‐Shaw, 2006; White, 1994, this study). Candidates for restratifying processes are, among many others, the along‐slope advection of stratification with the boundary current, the cross‐slope advection of buoyancy anomalies by Ekman transport, on timescales of a few days, (White, 1994, and the references therein), or, on subtidal time scales, an episodic straining of the near‐bottom isopycnals induced by the interaction of tidal currents with the sloping topography (Schulz & Umlauf, 2016; Schulz et al., 2017; Umlauf & Burchard, 2011; White, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Data collected during drift stations is always influenced by a combination of spatial and temporal variability, and a discrimination between both is often difficult. The drift track during the 10 h station was clearly influenced by tidal motions (see Figure 10), and tides are known to play an important role in this region (Janout & Lenn, 2014) and influence the near‐bottom dynamics in regard to both stratification and mixing (Schulz & Umlauf, 2016; Schulz et al., 2017; Umlauf & Burchard, 2011). Some lines of evidence, however, point to spatial variations as main cause for the observed variability: First, the modeled tidal current as well as the drift did not change direction or speed during the passage of the topographic sill (between 13:00 and 14:00), where high heat fluxes are observed, and second, after the drift and the tidal current changed direction at 19:00, a strongly stratified cold halocline layer and a temperature increase in the near‐bottom layer became visible, a vertical structure similar to conditions observed before the turning point of the drift was reached.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We refer to this mechanism as the slope-induced tidal straining (SITS) to distinguish this process from the classical tidal straining (CTS), which requires the presence of a horizontal density gradient. Recent idealized simulations showed that the presence of SITS could result in the upslope transport of SPM under a wide range of conditions, which shares many similarities with the tidal pumping induced by CTS (Schulz & Umlauf, 2016;Schulz et al, 2017).…”
Section: Introductionmentioning
confidence: 98%
“…Thus, understanding sediment dynamics is of considerable ecological and economical importance. Sediment transport is modulated by a variety of physical processes, including tides, river discharge (Allen et al, 1980;Gong et al, 2014), winds (Chen & Sanford, 2009a), baroclinic circulation (Meade, 1969;Wei et al, 2018), Earth's rotation (Huijts et al, 2006;Schulz et al, 2017), waves (George et al, 2018;Hoefel, 2003), geometry and bathymetry (Ralston et al, 2012;Kumar et al, 2017), tidal asymmetries in mixing (Scully & Friedrichs, 2007a, 2007bSommerfield & Wong, 2011;Gong et al, 2016), and settling and erosion lags (Cheng & Wilson, 2008;Chernetsky et al, 2010). The effects of river discharge, tides, and waves on sediment dynamics have been intensively studied.…”
Section: Introductionmentioning
confidence: 99%